Indigenous Cultural Identity of Research Authors Standard: research and reconciliation with Indigenous Peoples in rural health journals - Mark Lock; Faye McMillan; Donald Warne; Bindi Bennett; Jacquie Kidd; Naomi Williams; Jodie Martire; Paul Worley; Peter Hutten-Czapski; Emily Saurman; Veronica Mathews; Emma Walke; et al. (Rural and Remote Health, 2022)
The Indigenous Cultural Identity of Research Authors Standard (ICIRAS) is based on a gap in research publishing practice where Indigenous peoples' identity is not systematically and rigorously recognised in rural health research publications. There are widespread reforms, in different research areas, to counter the reputation of scientific research as a vehicle of racism and discrimination.